Attributes of Coffee Shop as Antecedent of Customer Satisfaction - Sofian; Ridwan Darussalam; Febriyanto Sasongko; Saga Hayyu Suyanto Putra; Tatang Mustaqim (Journal of Business and Behavioural Entrepreneurship, 2020)
Purpose – This study was conduct to examine the effect of attributes coffee shop to customer satisfaction in Indonesian coffee shop industry. Furthermore, this study is also examined customer loyalty as consequences of customer satisfaction Research Design – Five attributes of coffee shop were identified as having potential to be antecedent of customer satisfaction. The five attributes were: store atmosphere, employee attitude, IT service, coffee quality, and price fairness. Research Methodology – This study used online questionnaire which is adopted from the previous studies. The online questionnaires were used Google Form and shared through various social media platform. A total 851 respondents from 34 province in Indonesia were involved but only 350 respondents were qualified. KMO Factor analysis and regression analysis were performed to identify the validity of items and examine the relationship among variables. Findings – The results revealed that five of six hypothesized were statistically significant. Coffee quality was recognized as attribute of coffee shop which is produce the highest effects to customer satisfaction. Moreover, the relationship between customer satisfaction and customer loyalty was found positive.